ATOMIC STRUCTURE–THE ADVANTAGES NANOTECHNOLOGY E-MODULE DEVELOPMENT ACCORDING TO INDEPENDENT CURRICULUM FOR PHASE E STUDENTS OF SMA/MA - Ayu Permata Sari (Universitas Negeri Padang, 2023)
The independent curriculum was developed as a flexible framework, focusing on essential material, character development and student competencies. One of the essential materials studied in this curriculum is atomic structure-advantages of nanotechnology. This material is difficult for students, especially in the sub-material for determining electron configurations, sorting, classifying and differentiating the periodicity of elements in the periodic system. Teaching materials are needed to help students understand this material. This study aimed to develop an e-module of the atomic structure-advantages of nanotechnology for Phase E SMA/MA students and to analyze its level of validity and practicality. The type of research is Educational Design Research with the Plomp development model. The study is limited to the e-module practicality stage in small groups. The research subjects were UNP chemistry lecturers, teachers and Phase E students at SMAN 7 Padang. Data validation results were analyzed using Aiken's V formula, which shows that the e-module is valid with a value of V=0.82. Practicality test results data were analyzed using the percentage formula. They obtained practicality tests on teachers by 92% and students by 85% in small groups indicating that the e-modules produced were very practical.